Wetland city accreditation in Nepal: an approach to wetland management for livable cities and urban resilience - Shah, Deep Narayan; Paudel, Jhalak; Tachamo-Shah, Ram Devi; Dixit, Kanchan Mani; Sada, Rajesh (Banko Janakari, 2023)
The Ramsar Wetland City Accreditation encourages conservation and wise use of urban and peri-urban wetlands and promotes sustainable socio-economic benefits for local communities. It recognizes cities that value and protect their wetlands, fostering positive relationships with these ecosystems and increasing awareness in municipal planning and decision-making processes. A city's commitment to wetland conservation, awareness, active engagement in sustainable practices, and integration of wetland conservation into planning makes it a strong candidate for this recognition. Currently, 43 cities worldwide have achieved this accreditation since 2017; however, Nepalese cities, endowed with rich wetlands, are yet to be accredited. This study delves into the wetland-rich cities of Nepal, identifying five potential candidates for accreditation based on a comprehensive assessment. Following the assessment aligned with the Ramsar Convention requirements, Pokhara City (Kaski district) emerged as the top candidate for Ramsar Wetland City Accreditation in Nepal. The subsequent rankings include Sandakpur Rural Municipality (Ilam district), Bharatpur Metropolitan City (Chitwan district), Ghodaghodi Municipality (Kailali district), and Kapilvastu Rural Municipality (Kapilvastu district), respectively.